BRIEF CHARACTERISTICS OF RABIES NOZOAREALA - R. A. Nuratinov (Юг России: экология, развитие, 2014)
The article gives rabies's history in Russia in the world. Mortality of animals against rabies and how it spread in the mountainous country are characterized.